2018
DOI: 10.1007/s11069-018-3349-1
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing real options in urban surface water flood risk management under climate change

Abstract: Developing an adaptation option is challenging for long-term engineering decisions due to uncertain future climatic conditions; this is especially true for urban flood risk management. This study develops a real options approach to assess adaptation options in urban surface water flood risk management under climate change. This approach is demonstrated using a case study of Waterloo in London, UK, in which three Sustainable Drainage System (SuDS) measures for surface water flood management, i.e., green roof, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 28 publications
(40 reference statements)
0
30
0
Order By: Relevance
“…According to Jenkins et al [34], climate change and the rapid urbanization will be the two main factors responsible for increased flood rates in the coming decades. For this reason, the application of an approach that determines the impact of climate change on the future flood scenarios in Villahermosa, similar to the one proposed by Liu et al [35], is a crucial aspect to be considered in further developments of this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Jenkins et al [34], climate change and the rapid urbanization will be the two main factors responsible for increased flood rates in the coming decades. For this reason, the application of an approach that determines the impact of climate change on the future flood scenarios in Villahermosa, similar to the one proposed by Liu et al [35], is a crucial aspect to be considered in further developments of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this approach is a speed increase versus traditional modelling techniques, enabling development and analysis of many interventions and rainfall scenarios (Liu et al 2018). Previous research has identified comparable accuracy with a 5 to 20 time speed increase using CADDIES compared with other models such as Infoworks ICM (Gibson et al 2016;Wang et al 2018).…”
Section: Evaluating Many Strategies Using a Rapid Scenario Screening mentioning
confidence: 99%
“…Some of the studies on flood risk control focused on other types of uncertainty and did not explicitly consider climate uncertainty. Park et al ( 2014 ), Kim et al ( 2018 ) and Liu et al ( 2018 ) emphasized the importance of market uncertainty and temporal flexibility when timing investments in flood control. They used binomial lattices, decision trees and Monte Carlo simulations as solution methods.…”
Section: Real-options Analysis Of Investment In Climate Change Adaptamentioning
confidence: 99%